Fundos de pensão : um caminho socioeconomicamente viável? - Vaccaro, Stefania Becattini (2009)
This dissertation examines the development of private pension plans in Brazil and its close links with the economy. Search analyze the arguments in defense of its expansion, i.e. the growing pension deficit, the increase in population longevity, the benefits of encouraging the consolidation of a saving to finance economic development and increase the sharing of wealth with the workers by property the securities business. In that sense, this work takes care of the first financial architecture today, following an analysis of mechanisms of structuring and operation of pension funds and then stick it to study the production of wealth and of contemporary transformations of capitalism in order to discuss the production in the knowledge society and the impact of change in the regulations of collective social protection. The results show that the choice of the closed private pension, is a policy option that can bring serious social consequences.